2019
DOI: 10.7150/ijms.29560
|View full text |Cite
|
Sign up to set email alerts
|

Deduction of Novel Genes Potentially Involved in Upper Tract Urothelial Carcinoma Using Next-Generation Sequencing and Bioinformatics Approaches

Abstract: Upper tract urothelial carcinoma (UTUC) is a relatively uncommon cancer worldwide, however it accounts for approximately 30% of urothelial cancer in the Taiwanese population. The aim of the current study is to identify differential molecular signatures and novel miRNA regulations in UTUC, using next-generation sequencing and bioinformatics approaches. Two pairs of UTUC tumor and non-tumor tissues were collected during surgical resection, and RNAs extracted for deep sequencing. There were 317 differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Differentially expressed miRNAs greater than 2.0‐fold changes between young and senescent cell groups were indicated with reads per million (RPM) > 10 (Figure 1A). 20 …”
Section: Methodsmentioning
confidence: 99%
“…Differentially expressed miRNAs greater than 2.0‐fold changes between young and senescent cell groups were indicated with reads per million (RPM) > 10 (Figure 1A). 20 …”
Section: Methodsmentioning
confidence: 99%
“…Only select transcripts and pathways, such as hepatocyte growth factor and tumor necrosis factor (TNF) signaling or genes involved in adhesion, were differentially dysregulated between the two [36][37][38], but with a clear separation from renal cell carcinoma [39]. In a small study comparing healthy urothelial tissue and UTUC expression profiles, the authors mainly reported differences in the cell cycle and extracellular matrix-regulated genes [40].…”
Section: Rna Expression Profiles Of Utucmentioning
confidence: 99%
“…The difference of miRNA expression level between two groups more than twofolds were considered as significance (Figure 1C ). 25 , 30 …”
Section: Methodsmentioning
confidence: 99%